Estimation of aboveground biomass and carbon stock in Damas Beach, Trenggalek District, East Java, Indonesia - Nur, Alya Afra Inas; Arifiani, Kirana Nurul; Ramadhani, Ananda Rilo; Sabrina, Agra Dewi; Nugroho, Gilang Dwi; Kusumaningrum, Lia; Ramdhun, Devesee; Bao, Tran Quang; Yap, Chee Kong; Budiharta, Sugeng; Setyawan, Ahmad Dwi (Society for Indonesian Biodiversity, 2023)
Vegetation plays a vital role in providing environmental services in the form of storing carbon which can mitigate climate change. This study aimed to calculate Aboveground Biomass (AGB) and carbon stock in Damas Beach, Trenggalek District, East Java Province, Indonesia using an allometric equation. Biomass and carbon data at a tree (dbh >20 cm) and pole (dbh 10-20 cm) levels were collected using sampling plots distributed randomly at three stations, namely mangrove vegetation (Station I), coconut plantation (Station II), and agroforestry (Station III). The results showed that across the three research stations, there were a total of 23 plant species classified as tree and pole levels. At tree level, Rhizophora stylosa Griffith had the highest carbon stock with a value of 85.48 MgC/ha, while the lowest value was Nypa fruticans Wurmb with 0.02 MgC/ha. Similarly, at the pole level, the species with the highest carbon stock was R. stylosa, with a value of 65.88 MgC/ha, and the lowest was Theobroma cacao L. with 0.11 MgC/ha. The mangrove vegetation (Station I) had the highest carbon stock value of 200.53 MgC/ha. In contrast, the coconut plantation vegetation (Station II) has the lowest total carbon stock, with a value of 84.68 MgC/ha. Conservation and management need to be improved in the Damas Beach area because if the area is disturbed, the ability of vegetation to absorb carbon will decrease.